Delayed surgical and non-surgical treatment of placental remnants: no difference was found in the clinical efficacy and long-term pregnancy outcomes - Chen W; Zhang Z; Liu X (Dove Medical Press, 2018)
Weilin Chen, Zhibo Zhang, Xinyan Liu Department of Obstetrics and Gynaecology, Peking Union Medical College Hospital, Beijing, People’s Republic of China Purpose: In a tertiary hospital, patients facing delayed treatment with placental remnants were common. The aim of this study was to assess the clinical efficacy and long-term pregnancy outcomes of the delayed surgical/non-surgical treatment for placental remnants. Patients and methods: The records of referral patients with placental remnants after second/third-trimester delivery/termination of pregnancy were retrospectively analyzed. A long-term follow-up was made by phone to inquire about the future pregnancy outcomes. The measurements of clinical efficacy included the postpartum intervals for Doppler ultrasound to become normal and for menstrual cycle to return to normal. Conception rate, interval for future pregnancy and obstetric outcomes were used to assess future pregnancies. Results: A total of 65 patients, who were clinically diagnosed with placental remnants after termination of pregnancy at the second or third trimester from 2000 to 2016, were included in this study. Delayed surgical treatments employed at a median interval (MI) of 2.7 months after termination of pregnancy had a similar interval for ultrasound (P=0.353) and menstrual cycle (P=0.751) to return to normal compared with non-surgical treatments. For non-lactating patients who accepted expectant treatments, the postpartum interval for ultrasound to return to normal was significantly longer than that for menstrual cycle to become normal (MI=3.6, 1.5 months, respectively, P=0.000). For all of the patients successfully treated, the conception rate (P=1.00), the interval for a second pregnancy (P=0.771), ongoing-pregnancy/live birth rate (P=0.419) and the recurrence rate of placenta accrete (P=1.00) there was no significant difference between non-surgical and surgical treatments. Assisted selective uterine artery embolization at an MI of 23 days after the termination of pregnancy had a longer interval for ultrasound to become normal than single expectant treatment (P=0.017). For all patients after expectant treatments, 94.1% of patients conceived after an MI of 12.5 months with the ongoing-pregnancy/live birth rate of 66.7% and a 33.3% recurrence rate of placenta accreta. Conclusion: According to our experience, delayed surgeries at a postpartum interval of 2.7 months might have similar clinical efficacy and long-term pregnancy outcomes with expectant treatment in treating placental remnants. Keywords: placental remnants, clinical efficacy, reproductive outcome, conservative treatment, surgical treatment, placental remains